Arraste via fecal de nutrientes da ingestão produzido por bagaço de mandioca hidrolisado - Raupp, Dorivaldo da Silva; Marques, Silvia Helena de Paula; Rosa, Danielle Amorim; Caldi, Carla Marielle; Cremasco, Ana Candida Vivan; Banzatto, David Ariovaldo [UNESP] (Universidade de São Paulo (USP), Escola Superior de Agricultura Luiz de Queiroz (ESALQ), 2002)
A ingestão de fibras alimentares pode resultar em arraste de outros nutrientes para as fezes. Bagaço de mandioca produzido por polvilheira foi submetido à hidrólise enzimática para obtenção de um produto mais concentrado em fibra alimentar insolúvel denominado de bagaço de mandioca hidrolisado (BMH). O BMH foi avaliado em ensaios biológicos com ratos Wistar quanto a sua habilidade de arrastar os nutrientes da ingestão para as fezes, tendo como padrão de fibra o farelo de trigo (FT). Acréscimo à dieta base, substituindo igual quantidade de amido, de dose de 5%, 15% ou 25% de BMH promoveu arraste significativo de minerais (globalidade) ou proteína; dose de 15% ou 25% promoveu arraste significativo de lipídeo; e, dose de 25% promoveu arraste significativo de carboidrato digestível. Dose de 25% de FT produziu arraste significativo de minerais (globalidade), proteína ou carboidrato digestível, mas, o lipídeo não foi arrastado. BMH produziu efeito mais pronunciado que FT em arrastar minerais (globalidade) ou proteína para a dose de 5% ou 15%; no entanto, para a dose alta, de 25%, as fontes produziram efeitos semelhantes em arrastar a proteína, mas o FT promoveu maior arraste de minerais (globalidade). Não houve diferença entre fontes, BMH e FT, em arrastar lipídeo ou carboidrato digestível para as fezes. Na dose alta (25%) o BMH promoveu efeitos, no máximo, semelhantes ao FT, em arrastar para as fezes os nutrientes da ingestão; assim, é recomendado como fonte alternativa de fibra alimentar insolúvel para a formulação de alimentos funcionais-digestivos.

Dietary fiber can drag nutrients in faeces. Cassava waste from starch industry can be hydrolyzed by an enzymatic process and give origin to a food with high content of insoluble dietary fibers, named partially hydrolyzed cassava waste (HCW). HCW or standard wheat bran (WB) were fed to model growing rats in order to assess their dragging skill of nutrients from the intake of faeces. Addition of 5%, 15% or 25% HCW, in replacement of starch, promoted a significant dragging proportion for the overall minerals or proteins; addition of 15% or 25% HCW dragged a significant proportion of lipids and the addition of 25% HCW dragged a significant proportion of digestible carbohydrates. Adding 25% WB caused significant dragging of total minerals, protein and digestible carbohydrates, lipids were, however, not dragged with WB treatment. HCW promoted a more pronounced effect as compared to WB in regard to the dragging process of total minerals or proteins for 5% or 15% additions. Nervertheless, for high rates, such as 25% additions, both fibrous sources produced similar effects on the dragging of protein, but WB promoted the greatest dragging process of total minerals. No differences between both fiber sources were observed as to their abilities of dragging lipids or digestible carbohydrates into faeces. With high rates (25%) HCW promoted effects similar to WB, allowing to conclude that HCW might be used as an important alternative source of insoluble dietary fiber for the formulation of digestive-functional feeds.
Nutrient dragging in faeces from the intake of partially hydrolyzed cassava waste
Keywords: cassava; Dietary fiber; wheat bran; Nutrition; functional food; mandioca; fibra alimentar/dietária; farelo de trigo; Nutrição; alimento funcional